Highly Transparent, Deformable, and Multifunctional AgPdCu/ITO/PTFE Hybrid Films for Self‐Cleaning, Flexible, and Energy‐Saving Smart Windows. Issue 22 (19th September 2018) - Lee, Sang‐Mok; Park, Jin‐Yeong; Kim, Han‐Ki
Abstract: Rollable, bendable, twistable, and foldable polymer–oxide–metal multistacked hybrid films are demonstrated, which simultaneously act as multifunctional electrodes in flexible polymer‐dispersed liquid crystal (PDLC) windows and flexible and transparent thin‐film heaters (TFHs) for self‐cleanable and flexible smart windows. By continuous sputtering of a thin polytetrafluoroethylene (PTFE)–indium tin oxide (ITO)–AgPdCu (APC) multilayer on a colorless polyimide substrate, transparent and multifunctional films are fabricated with a low sheet resistance of 7 Ω □ −1, high optical transmittance of 83% at a wavelength of 550 nm, low transmittance in the infrared region, and a high contact angle of 109°. Based on inner/outer bending, rolling, twisting, and folding tests, the outstanding flexibility of these PTFE/ITO/APC multistacked films is demonstrated. The flexible PDLC and flexible TFHs with PTFE/ITO/APC multistacked electrodes show a controllable transmittance range between the on and off states that is nearly 40%, and a high saturation temperature of 111 °C is observed at a low applied voltage of 4 V. The multifunctional properties of the flexible PDLC and TFHs fabricated on PTFE/ITO/APC hybrid films indicate that the polymer–oxide–metal hybrid film is a versatile transparent electrode that can be used for flexible, smart, and energy‐saving windows. Abstract : Highly deformable indium tin oxide (ITO)/AgPdCu (APC)/polytetrafluoroethylene (PTFE) and PTFE/ITO/APC multilayers on colorless polyimide substrates demonstrate heating operation over 100 °C at 4 V for transparent rollable heaters as well as off‐ and on‐state transmittance in rollable smart windows that are fabricated with a sandwich‐structured multilayer electrode, microsphere spacer, and polymer‐dispersed liquid crystal solution.